Strategi Pengembangan Produk, Branding, Labeling, dan Kewirausahaan Berbasis Manajemen, untuk Meningkatkan Kesejahteraan Pengusaha Kecil Penghasil Lanting di Desa Jetis Kecamatan Loano Kabupaten Purworejo - Murry Hermawan Saputra; Ridwan Baraba (Universitas Muhammadiyah Purworejo, 2017)
Service Programs of Science and Technology for the Community (IbM) was motivated by the circumstances of domestic industry (home industry scale) food products typical of the area called Lanting, in Jetis, District Loano, Purworejo, Central Java, which has yet to develop optimally. This is because the classical problems commonly faced SMEs, which limitations in terms of management, especially marketing management, financial management, production management, and human resource management. Service Programs of Science and Technology for the Community (IbM) aims to improve the productivity of domestic industry and income entrepreneurs lanting village Jetis, through the implementation of the program of training and provision of stimuli both physical and nonphysical, in the field of science and technology, marketing and bookkeeping in groups of partners , An important point that underlies the idea of ​​service programs, it is thought important to improve the ability to compete for entrepreneurs lanting in the village, to educate a good marketing strategy, including branding, labeling, packaging, promotion by means of conventional and via the internet, and more business governance in their businesses. IbM service programs that have been implemented have contributed to encouraging the artisans in the village Jetis Lanting become more independent, improve the capacity, capability, and quality of their products, so it can become a very competitive SMEs amid increasing competition in the business today.